Teachers' Obstacles in Creating History Learning Tools for the Kurikulum Merdeka at Senior High School 2 Ranah Batahan - Pono Pono; Meldawati Meldawati; Juliandr Kurniawan Junaidi (CV. Rayyan Dwi Bharata, 2024)
This research is motivated by seeing the implementation of the independence curriculum in schools in Indonesia. The research method is a qualitative research method using observation techniques, interviews, documentation studies. The subject of this study is Osfia Roza, a history subject educator at SMAN 2 Ranah Batahan. The results of this study are as follows:The research conducted, it is known that SMAN 2 Ranah Batahan has several problems in implementing history lessons, such as problems with the curriculum, problems from educators and students or from facilities and infrastructure. With this problem, the achievement of learning objectives is delayed, but by knowing what the problem is, we can compare more effective activities so that the objectives of learning can be realized.